Pola Komunikasi antara Pengasuh dan Anak Asuh dalam Pembinaan Kedisiplinan Hafalan Al Qur’an di Pondok Zawiyatul Huffazh Kecamatan Air Joman - Lakum Lakum; Nurhana Rambe; Mega Lestari (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Children in the Air Joman sub-district attend school in Pondok Zawiyatul Huffazh, a non-formal education institution that teaches subjects based on the Qur'an. This pesantren emphasizes reading and memorizing the Qur'an more than anything else. Discipline in memorizing children's verses of the Qur'an is largely influenced by the communication style of caregivers and children they care for. This study focuses on communication patterns that foster discipline in memorizing the Qur'an between foster children and their caregivers, communication methods that foster discipline in memorizing the Qur'an between foster children and their caregivers, as well as supporting and inhibiting factors. patterns of communication between foster children and caregivers. Researchers used qualitative research methods in this study. where observation, interviews with various informants, and documentation were used to collect data Information collection was carried out through direct perception in the field, as well as direct inclusion with the guardians and principals of Zawiyatul Huffazh's life experiences. In addition, this study refers to Josep A. Devito's theory of communication patterns which states that there are five kinds of communication patterns: circle patterns, chain patterns, wheel patterns, and star patterns. The purpose of this study is to find out more about the communication patterns that exist between foster children in coaching in Air Joman District and their caregivers. Through this study, the findings from interviews and observations can also be examined to find out whether communication patterns have sufficient impact on the practice of memorizing the Qur'an.